Costos De Producción De La Compañía Becromal S.A. - Morales Sánchez, Lucy Tanya (2018)
Ecuador is considered as a predominantly agricultural nation, for its diverse regions, climates, soils, etc., therefore agriculture is one of the main productive engines of the economy, being an important component within the daily consumption of the population, demonstrates that the highest percentage of rice is produced in the coastal region. The present work establishes the application of the production costs that have as purpose to obtain the obtaining of great utilities by means of the agricultural activity, in this case they realize the cultivation of rice, reason why according to this observations were made in the company Becromal SA , the same ones that I will specify during the development of this investigation as it is the event of the omission of the elements of the cost of production such as the raw material (agricultural inputs), labor and indirect costs of production, implying that for the accountant It is very important to obtain this data, which allows you to measure in an efficient way the cost that has caused the company to produce your crop, taking into account that this information will be informed through the state of production costs, and the result of this state is used to calculate unit cost of agricultural production. Therefore, the agricultural product is measured to know the profit margin for each product, based on this for a correct presentation with real data recorded in the income statement, and that ultimately affects the realization of the statement of financial position. (balance sheet) of the company. All this information was based on the existing research model for the elaboration of case studies in the Engineering degree in Accounting and Auditing through the sub-line of Accounting Information Management